Annex IV: Modes of Variability - Cassou, Christophe (2021)
This Annex describes the fundamental features of the main modes of large-scale climate variability assessed across chapters in the AR6 WGI report. Modes are defined as recurrent space-time structures of variability of the climate system with intrinsic spatial patterns, seasonality and timescales. They can arise through the dynamical characteristics of the atmospheric circulation but also through coupling between the ocean and the atmosphere, with some interactions with land surfaces and sea ice. The variability of the climate system at ocean- or continental-basin scales, and in particular on seasonal-to-multidecadal timescales, can be described to a large extent by the occurrence and often combination of several modes of climate variability which lead to local impacts and remote responses through teleconnection processes on top of externally forced trends. More precisely, the concept of teleconnection refers to the ability of modes of variability to relate climate in remote regions through associated atmospheric or oceanic pathways. Regional climate variations are thus the complex outcome of local physical processes, such as thermodynamical and land-atmosphere feedback processes, and non-local large-scale phenomena.